(untitled) (Global Journal of Medical Research, 2023)
Infection of SARS-COV2 and its variants causes wide range morbidity and mortality in recent years. Identification of epitope-based mechanism of viral infection with progressive fatality and antiviral immunotherapy are two major goals to address population-bias immune response. We selected peptides from SARS-COV2 Spike (6VXX_A), Delta (B.1.617.2), Omicron (B.1.1.529) proteins. These peptides contain epitopes which are identified as low rank good fit immunogenic as recognized more by HLA-DRB1*15:01, than HLA-DRB1*07:01 and HLA-DRB1*03:01. We also found the selected epitopes specifically form interactive complex with mucosa-associated invariant T cell. The Molecular Docking and Molecular Dynamics experiments demonstrated amino acid sequence-specific interaction between close atoms from epitopes and MAIT-TCR. We used virus unrelated microbial peptide antigen85 as control.